Folic Acid Represses Hypoxia-Induced Inflammation in THP-1 Cells through Inhibition of the PI3K/Akt/HIF-1α Pathway. - Xiaoyan Huang; Zhiying He; Xinwei Jiang; Mengjun Hou; Zhihong Tang; Xiaozhou Zhen; Yuming Liang; Jing Ma (PLoS ONE)
Though hypoxia has been implicated as a cause of inflammation, the underlying mechanism is not well understood. Folic acid has been shown to provide protection against oxidative stress and inflammation in patients with cardiovascular disease and various models approximating insult to tissue via inflammation. It has been reported that hypoxia-induced inflammation is associated with oxidative stress, upregulation of hypoxia-inducible factor 1-alpha (HIF-1α), and production of pro-inflammatory molecules. Whether folic acid protects human monocytic cells (THP-1 cells) against hypoxia-induced damage, however, remains unknown. We used THP-1 cells to establish a hypoxia-induced cellular injury model. Pretreating THP-1 cells with folic acid attenuated hypoxia-induced inflammatory responses, including a decrease in protein and mRNA levels of interleukin (IL)-1β and tumor necrosis factor-alpha (TNF-α), coupled with increased levels of IL-10. Folic acid also reduced hypoxia-induced Akt phosphorylation and decreased nuclear accumulation of HIF-1α protein. Both LY294002 (a selective inhibitor of phosphatidyl inositol-3 kinase, PI3K) and KC7F2 (a HIF-1α inhibitor) reduced levels of hypoxia-induced inflammatory cytokines. We also found that insulin (an Akt activator) and dimethyloxallyl glycine (DMOG, a HIF-1α activator) induced over-expression of inflammatory cytokines, which could be blocked by folic acid. Taken together, these findings demonstrate how folic acid attenuates the hypoxia-induced inflammatory responses of THP-1 cells through inhibition of the PI3K/Akt/HIF-1α pathway.